2016
DOI: 10.1038/srep27872
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ROS mediates gas plasma-facilitated cellular transfection in 2D and 3D cultures

Abstract: This study reports the potential of cold atmospheric plasma (CAP) as a versatile tool for delivering oligonucleotides into mammalian cells. Compared to lipofection and electroporation methods, plasma transfection showed a better uptake efficiency and less cell death in the transfection of oligonucleotides. We demonstrated that the level of extracellular aqueous reactive oxygen species (ROS) produced by gas plasma is correlated with the uptake efficiency and that this is achieved through an increase of intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…In contrast with a previous study demonstrating low plasmid transfection efficiency (about 6%) in 3D cultures ( 30 ), we managed to reach plasmid extinction efficiency of more than 40%. Moreover, in a recent study ( 36 ) demonstrating the benefits of a novel gas plasma-facilitated cellular transfection method, siRNA extinction efficiency of about 20% (as compared to more than 80% in our system) and plasmid transfection efficiency of less than 5% (as compared to more than 40% in our system) were reached in a 3D culture system. Strikingly, we managed for the first time to reach siRNA transfection efficiencies that are comparable between 2D cultures and 3D organoids.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast with a previous study demonstrating low plasmid transfection efficiency (about 6%) in 3D cultures ( 30 ), we managed to reach plasmid extinction efficiency of more than 40%. Moreover, in a recent study ( 36 ) demonstrating the benefits of a novel gas plasma-facilitated cellular transfection method, siRNA extinction efficiency of about 20% (as compared to more than 80% in our system) and plasmid transfection efficiency of less than 5% (as compared to more than 40% in our system) were reached in a 3D culture system. Strikingly, we managed for the first time to reach siRNA transfection efficiencies that are comparable between 2D cultures and 3D organoids.…”
Section: Discussionsupporting
confidence: 50%
“…This can be done by omics techniques 30 31 32 and/or up or downregulation of target genes using siRNA (redox) signaling inhibitors, antioxidants and antioxidant enzymes, as well as modulation of the plasma's reactive species output. 33 34 35 Hence, streamlined assay protocols are needed to test larger sample sets with large numbers of iterations.…”
Section: Discussionmentioning
confidence: 99%
“…Among APP medical applications, transfection technology of middle‐size (500–30 000 Da) and large‐size (30 000‐ Da) molecules has attracted attention. Some research groups have reported cell membrane permeabilization of middle‐size fluorescent dye and large‐size plasmid DNA using various types of APP . Although a few reports have suggested that the multiple effects of electric and chemical stimuli are key factors in APP‐induced membrane permeabilization, most of the underlying mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%